Incidence of tuberculosis in enlarged neck nodes, our experience - Maharjan, M; Hirachan, S; Kafle, PK; Bista, M; Shrestha, S; Toran, KC; Lakhey, M (Kathmandu University Medical Journal, 2009)
Objectives: To determine the incidence of tuberculous lymphadenitis in enlarged neck nodes. Materials and methods: Continuous prospective study is carried out in the department of otorhinolaryngology head & neck surgery, Kathmandu Medical College, Kathmandu, during two years, from January 2006 to January 2008. The study included a group of 155 patients with cervical lymphadenopathy. Each patient underwent a detail clinical Ear, Nose and Throat (ENT) examination and a battery of investigations which included Fine Needle Aspiration Cytology (FNAC) of the nodes, Montoux’s test, blood Erythrocyte Sedimentation Rate (ESR) and chest X-ray. Those patients with tubercular lymphadenitis were referred to Directly Observed Therapy System (DOTS) clinic for anti-tubercular therapy. Others with reactive lymphadenitis were treated with antibiotic and those with metastatic neck nodes were treated accordingly. Results: Of the 155 cases with enlarged neck nodes, 83 (54%) had tubercular lymphadenitis. Fifty two (33%) cases had reactive lymphadenitis and 17 (11%) cases were diagnosed with metastatic neck nodes. Fine needle aspiration cytology was found to be highly effective in the diagnosis of tubercular lymphadenitis with 94% accuracy. Majority of patients were otherwise healthy adults, aged between 8 - 71 years. No difference was observed between male and female in this study. Posterior triangle (PT) nodes were most commonly affected group of nodes accounting for 35 (42%) cases and preauricular region 1 (1%) case being the least commonly affected site. Fifteen (18%) cases presented with abscess formation. Only 42 (50%) cases had family history of tuberculosis but 8 (9%) patients had previous history of various forms of tuberculosis. Twelve (14%) patients had positive chest X-ray findings suggesting of concurrent pulmonary tuberculosis. All the patients were referred to DOTS clinic and were treated with category (CAT) - III anti tubercular therapy (ATT). Others with concurrent pulmonary tuberculosis were treated with CAT I regime. None of the patients required surgical treatment. Conclusion: There is high incidence of tubercular cervical lymphadenitis in patients with enlarged neck nodes in developing countries like Nepal. Involvement of cervical lymphnodes are the most commonly affected group of nodes. Therefore, it is important that otolaryngologists are aware of tuberculosis in the head and neck region. Key words: Tuberculosis, Lymph node, Fine needle aspiration cytology, Lymphadenitis doi: 10.3126/kumj.v7i1.1766 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 54-58